Simultaneous screening and analysis of antiplatelet aggregation active alkaloids from Rhizoma Corydalis. (1st December 2016) - Zhang, Qian; Chen, Cen; Wang, Feng-Qin; Li, Chun-Hong; Zhang, Qi-Hui; Hu, Yuan-Jia; Xia, Zhi-Ning; Yang, Feng-Qing
Abstract: Context: The rising problem of atherosclerosis and ischemic heart disease emphasizes the need to look for new antithrombotic components with effective modes of action. Corydalis yanhusuo (Y.H. Chou & Chun C. Hsu) W.T. Wang ex Z.Y. Su & C.Y. Wu (Papaveraceae) (Rhizoma Corydalis) has been used in the traditional medicines for the treatment of cardiovascular disease. Objective: The antiplatelet aggregation compounds in Rhizoma Corydalis were screened to validate its traditional medicinal use. Material and methods: Total alkaloid extract (TAE) of Rhizoma Corydalis was obtained by refluxing 100 g Rhizoma Corydalis powder with 600 mL 70% ethanol, and purified by acidification (20% HCl) and alkalization (5 M NaOH) process. Potential antiplatelet aggregation compounds in TAE were screened by a method involving platelet bio-specific extraction and HPLC-DAD/LC–MS analysis. Further in vitro antiplatelet aggregation activity confirmation of TAE and seven main alkaloids were achieved by turbidimetry method within 3 h after blood collection from rabbit carotid artery, and all the test drugs were at the concentration range of 25–350 μg/mL. Finally, HPLC-DAD was employed for the quantitative determination of seven main components in TAE. Results: Five alkaloids, identified as glaucine, dehydrocorydaline, canadine, tetrahydrocoptisine and corydaline, can be specifically extracted with platelets. The results indicated that all these five alkaloids can inhibit thrombin-induced platelet aggregation in a low dose (IC50 of glaucine, dehydrocorydaline, canadine, tetrahydrocoptisine and corydaline were 49.057, 34.914, 33.547, 84.261 and 54.164 μg/mL, respectively) as compared to TAE (IC50 = 175.426 μg/mL) and aspirin (IC50 = 300.340 μg/mL), while the unbound compounds (palmatine and tetrahydropalmatine) had a very weak antiplatelet effect (IC50 > 200 μg/mL). Discussion and conclusion: This study is the first reported work for antiplatelet components screening in Rhizoma Corydalis. Seven compounds were detected and identified by HPLC-DAD/LC–MS, of which five platelet-targeted compounds were discovered.